Hadron spectroscopy from lattice quantum chromodynamics - RYAN, SINEAD (My University, 2016)
Lattice calculations of hadron spectroscopy are discussed. A brief introduction to numerical simulations of QCD, with a focus on spectroscopy is given. Results for spectroscopy of low-lying, excited and exotic states including hybrids and the X; Y; Z states in charmonium are described. New developments that have allowed for determinations of scattering parameters, including in a coupled-channel analysis are briefly described providing a roadmap for future lattice calculations of excited and exotic states.
EPJ Web of Conferences
MESON 2016 14th International Workshop on Meson Production, Properties and Interaction
PUBLISHED
Export Date: 6 January 2017
Keywords: Lattice calculations; Lattice calculations